Hospital Digitalization And Patient Satisfaction: The Mediating Role Of Operational Efficiency In Jakarta - Melly Melly; Mohammad Agung Saryatmo (UNIVERSITAS PAKUAN, 2025)
This study aims to empirically investigate the impact of hospital digitalization as an independent variable, patient satisfaction as a dependent variable, with operational efficiency acting as a mediating variable. Employing a quantitative methodology, the research utilizes explanatory research to examine the causal relationships among sample variables through a survey conducted with 105 respondents who have received services from hospitals equipped with digital technology. A questionnaire featuring Likert scale-based questions was utilized for data collection. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that digitalization in hospitals influences patient satisfaction, with operational efficiency significantly mediating the relationship between digitalization and patient satisfaction. The implications of this study for hospital management include the importance of prioritizing investments in digital infrastructure development and enhancing human resource capacity to optimize the implementation of digital transformation. This study establishes that digitalization extends beyond mere technological innovation; it constitutes a strategic element that plays a vital role in significantly enhancing the quality of health services and overall hospital performance.